Atmospheric methane oxidizers are present and active in Canadian high Arctic soils. Issue 2 (19th February 2014) - Martineau, Christine; Pan, Yao; Bodrossy, Levente; Yergeau, Etienne; Whyte, Lyle G.; Greer, Charles W.
Abstract The melting of permafrost and the associated potential for methane emissions to the atmosphere are major concerns in the context of global warming. However, soils can also represent a significant sink for methane through the activity of methane‐oxidizing bacteria (MOB). In this study, we looked at the activity, diversity, and community structure of MOB at two sampling depths within the active layer in three soils from the Canadian high Arctic. These soils had the capacity to oxidize methane at low (15 ppm) and high (1000 ppm) methane concentrations, but rates differed greatly depending on the sampling date, depth, and site. The pmoA gene sequences related to two genotypes of uncultured MOB involved in atmospheric methane oxidation, the 'upland soil cluster gamma' and the 'upland soil cluster alpha', were detected in soils with near neutral and acidic pH, respectively. Other groups of MOB, including Type I methanotrophs and the 'Cluster 1' genotype, were also detected, indicating a broader diversity of MOB than previously reported for Arctic soils. Overall, the results reported here showed that methane oxidation at both low and high methane concentrations occurs in high Arctic soils and revealed that different groups of atmospheric MOB inhabit these soils.